2005
DOI: 10.1007/s00535-005-1599-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of pseudomembranous colitis with Henoch-Schönlein purpura

Abstract: A 79-year-old man was admitted because of cholecystitis that occurred about 40 days after sigmoidectomy had been performed for colonic cancer. Though antibiotics improved his condition, the patient had hematochezia, diarrhea, and left lower abdominal pain. Colonoscopic findings showed multiple ring-like areas of redness and petechiae in the rectosigmoid colon and marked edema from the descending to the transverse colon. The patient then developed purpura on the extensor surfaces of the legs and bilateral gonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Whether these diseases are truly linked to HSP or occur together coincidentally is unknown. Clostridium difficile-related pseudomembranous enteritis can develop with [47] or after [48] HSP. HSP may also be found in about 5% of patients with familial Mediterranean fever (FMF) with an increased frequency of the mutations associated with FMF [49].…”
Section: Triggers Of Hspmentioning
confidence: 99%
“…Whether these diseases are truly linked to HSP or occur together coincidentally is unknown. Clostridium difficile-related pseudomembranous enteritis can develop with [47] or after [48] HSP. HSP may also be found in about 5% of patients with familial Mediterranean fever (FMF) with an increased frequency of the mutations associated with FMF [49].…”
Section: Triggers Of Hspmentioning
confidence: 99%
“…IgA vasculitis complicated by Clostridium difficile infection (CDI) is extremely rare. To our knowledge, so far, there are only four cases in children and one in an adult published in the literature [9][10][11][12]. This makes our case the second of its type (in an adult with IgA vasculitis complicated by CDI) reported in the literature.…”
mentioning
confidence: 68%
“…To the best of our knowledge, this is the second published case of IgA vasculitis complicated by CDI in adults. Upon a thorough search, we found only five cases reported so far: four children [9][10][11] and one adult [12]. The authors suggested that antibiotic therapy, intestinal lesions (mucosal ischemia) caused by IgA vasculitis and corticosteroid therapy could have led to a change in intestinal microbiota and, consequently, to overgrowth of C. difficile, increasing the risk of CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Then again, intestinal manifestations of Henoch-Schönlein purpura also can predispose patients to pseudomembranous colitis, so the direction of causality is uncertain. 12…”
Section: Diagnosismentioning
confidence: 99%